Development of the Massive Open Online Course (MOOC) Module for English for Academic Purposes Course - Rahman Hakim; Rosmania Rima (English Department - University of Sultan Ageng Tirtayasa, 2024)
This study intends to develop Massive Open Online Course (MOOC) Module for English for Academic Purposes Subject at Sultan Ageng Tirtayasa University. The MOOC aims to equip learners, regardless of department, faculty, or participating campus, with the necessary English language skills to succeed in an academic environment. In order to improve the effectiveness of online learning from these courses, an e-learning platform, such as MOOC, that can accommodate a large number of students from departments and faculties, as well as from other campuses that are members of the Study Program Implementing Collaborative Free Learning Curriculum - Independent Campus